Heterostructure nanoarchitectonics with ZnO/SnO2 for ultrafast and selective detection of CO gas at low ppm levels. Issue 24 (15th December 2022) - Mauraya, Amit Kumar; Mahana, Debashrita; Jhaa, Gaurav; Pradhan, Bipul Kumar; Roopa,; Tomer, Shweta; Vandana,; Singh, Preetam; Kushvaha, Sunil Singh; Muthusamy, Senthil Kumar
Abstract: Heterojunction-based gas sensors are very attractive as they substantially improve the sensing characteristics due to the effective potential barrier present at the interface. Taking the advantages of two excellent semiconducting gas sensing materials i.e., SnO2 and ZnO, herein, we have constructed ZnO/SnO2 heterojunction by the combination of vacuum evaporation and r.f. sputtering or atomic layer deposition techniques. The ZnO/SnO2 heterostructure with optimized thickness of ZnO (∼10 nm) shows a 6-fold enhancement in sensing response compared to bare SnO2 films against CO gas. The sensing responses of 81 and 85 % have been obtained for ZnO/SnO2 heterostructures with ZnO deposited by sputtering and atomic layer deposition (ALD) methods, respectively, against 91 ppm of CO gas with an estimated limit of detection of 1.67 and 0.37 ppm. The ALD ZnO/SnO2 sample displays an extremely fast response time of 5 s. The heterostructure sensors are also highly selective towards CO gas in the presence of other interfering toxic agents. The enhanced sensing characteristics of ZnO/SnO2 are assigned to the formation of n-n heterojunction as depicted by X-ray photoelectron spectroscopic band alignment study and the strong CO adsorption on ZnO surface as derived from density functional theory calculations.